DEVELOPMENT OF INTERCULTURAL COMMUNICATION AMONG STUDENTS IN RUSSIAN LANGUAGE CLASSES BASED ON INNOVATIVE PEDAGOGICAL TECHNOLOGIES (World Bulletin of Social Sciences, 2024)
This study explores the development of intercultural communication skills among students in Russian language classes through the implementation of innovative pedagogical technologies. By investigating the impact of these technologies on students' ability to communicate effectively across cultural boundaries, the research aims to enhance language learning outcomes and promote greater cultural awareness among learners. This study focuses on leveraging innovative pedagogical technologies to enhance students' ability to communicate effectively across cultural boundaries. By incorporating technology into language teaching, educators can create immersive and interactive learning experiences that simulate real-world communication scenarios. Virtual reality simulations, online collaboration platforms, and multimedia resources can provide students with opportunities to engage with authentic cultural content and practice their language skills in context. Through these innovative approaches, students can develop a deeper understanding of cultural nuances, improve their communication proficiency, and build confidence in cross-cultural interactions.